Landmark : the inside story of America's new health-care law and what it means for us all (PublicAffairs, 2010)
The Washington Post's must-read guide to the health care overhaul What now? Despite the rancorous, divisive, year-long debate in Washington, many Americans still don't understand what the historic overhaul of the health care system will - or won't - mean. In Landmark, the national reporting staff of The Washington Post pierces through the confusion, examining the new law's likely impact on us all: our families, doctors, hospitals, health care providers, insurers, and other parts of a health care system that has grown to occupy one-sixth of the U.S. economy. La.